Comparative study on corrosion characteristics of Al2O3/316L and TiO2/316L stainless steel in supercritical water. (3rd August 2017) - Wang, Yuzhen; Gao, Fen; Yang, Jianqiao; Zhu, Yitong; Fang, Changqing; Wang, Shuzhong; Zhao, Gaoyang
Abstract: Al2 O3 and TiO2 coatings were fabricated on 316L stainless steel by atmospheric plasma spraying to improve the corrosion resistance of 316L stainless steel in supercritical water. The corrosion characteristics of the samples were evaluated in a batch reactor at 500 °C and 25 MPa with an oxygen concentration of 1000 mg/L for 80 h. The adhesive strengths of the coated samples were tested, and the weight changes, morphologies and elements distributions of the fresh and corroded samples were analyzed. Results showed that the bond strength of TiO2 /316L was 1.5 times than that of Al2 O3 /316L (26.639 N/mm 2 ). The surface morphology of Al2 O3 /316L showed gully erosion with much pores and cracks after exposed in SCW, which provided channels for oxygen and SCW to get into the substrate and also the elements in substrate to diffuse to the surface of the coating. The corroded Al2 O3 /316L suffered significant weight loss, and most of the coatings were peeled off. However, the surface morphology of TiO2 /316L was relatively dense and the thickness of the coating was not found to decrease obviously. Highlights: Corrosion characteristics of Al2 O3 /316L and TiO2 /316L were evaluated in supercritical water. Gully erosion was found on the surface of Al2 O3 /316L, and most of the coating was peeled off. Surface morphology of TiO2 /316L was dense, and the thickness was not found to decrease obviously.